APPLYING CONTEXTUAL TEACHING AND LEARNING IN MASTERING THE PRESENT CONTINUOUS TENSE IN SECOND CLASS OF SMP NEGERI 35 MAKASSAR - Ahmat Setyanto (Teaching English as a Foreign Language Overseas Journal, 2020)
This study aims to know the effect of applying contextual teaching and learning in mastering the present continuous tense students. The study employed pre-experimental design. The population consists of 270 students and the sample were 23 students taken from the SMP Negeri 35 Makassar of grade eight. The data was collected by administering multiple choice test with consisting of 20 number. The T-Value of post-test is lower than ? (0,00<0,05) The result indicates that the alternative hypothesis(H1) is accepted and of course the null hypothesis (H?) is rejected, it shows that applying contextual teaching and learning has effect on students’ present continuous tense mastery